2020
DOI: 10.1111/irv.12729
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospitalized respiratory syncytial virus disease and its severe outcomes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Risk factors for RSV associated ALRI include prematurity, low birth weight, underlying congenital heart disease, chronic lung disease, and parental smoking (9,10). In addition, upregulation of proinflammatory interleukins (IL)-8, and macrophage inflammatory protein (MIP)-1a accompanied by a strong neutrophil infiltration are associated with severe RSV induced manifestations, such as bronchiolitis (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for RSV associated ALRI include prematurity, low birth weight, underlying congenital heart disease, chronic lung disease, and parental smoking (9,10). In addition, upregulation of proinflammatory interleukins (IL)-8, and macrophage inflammatory protein (MIP)-1a accompanied by a strong neutrophil infiltration are associated with severe RSV induced manifestations, such as bronchiolitis (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the World Health Organization (WHO) indicated a high priority on establishing global RSV disease surveillance systems, as well as robust age-specific estimations in order to determine the optimal age for immunization [ 16 ]. However, data on the prevalence of RSV and the burden of disease in healthy children are scarce, as most studies are conducted only in high-risk groups [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable to reviews of RSV CFRs for infants and children in high-income countries [ 10 , 55 ]. A German study of 8521 infants and children <5 years hospitalized with RSV reported an overall CFR of 0.12% [ 56 ]. However, this review also revealed that nationally representative estimates of RSV mortality for otherwise healthy, late preterm to full-term infants are limited and out of date (no available mortality rates; latest update through 2007 for mortality counts and update in 2013 for CFRs) or are not stratified by important demographic or clinical variables such as race or insurance payer.…”
Section: Discussionmentioning
confidence: 99%